Trends on Aspergillus Epidemiology—Perspectives from a National Reference Laboratory Surveillance Program - Raquel Sabino; Paulo Gonçalves; Aryse Martins Melo; Daniela Simões; Mariana Oliveira; Mariana Francisco; Carla Viegas; Dinah Carvalho; Carlos Martins; Teresa Ferreira; Cristina Toscano; Helena Simões; et al. (Journal of Fungi, 2021)
Identification of Aspergillus to species level is important since sibling species may display variable susceptibilities to multiple antifungal drugs and also because correct identification contributes to improve the knowledge of epidemiological studies. Two retrospective laboratory studies were conducted on Aspergillus surveillance at the Portuguese National Mycology Reference Laboratory. The first, covering the period 2017–2018, aimed to study the molecular epidemiology of 256 Aspergillus isolates obtained from patients with respiratory, subcutaneous, or systemic infections and from environmental samples. The second, using our entire collection of clinical and environmental A. fumigatus isolates (N = 337), collected between 2012 and 2019, aimed to determine the frequency of azole-resistant A. fumigatus isolates. Aspergillus fumigatus sensu stricto was the most frequent species in both clinical and environmental samples. Overall, and considering all Aspergillus sections identified, a high frequency of cryptic species was detected, based on beta-tubulin or calmodulin sequencing (37% in clinical and 51% in environmental isolates). Regarding all Fumigati isolates recovered from 2012–2019, the frequency of cryptic species was 5.3% (18/337), with the identification of A. felis (complex), A. lentulus, A. udagawae, A. hiratsukae, and A. oerlinghauensis. To determine the frequency of azole resistance of A. fumigatus, isolates were screened for azole resistance using azole-agars, and 53 possible resistant isolates were tested by the CLSI microdilution reference method. Nine A. fumigatus sensu stricto and six Fumigati cryptic isolates showed high minimal inhibitory concentrations to itraconazole, voriconazole, and/or posaconazole. Real-time PCR to detect cyp51A mutations and sequencing of cyp51A gene and its promoter were performed. The overall frequency of resistance to azoles in A. fumigatus sensu stricto was 3.0%. With this retrospective analysis, we were able to detect one azole-resistant G54R mutant A. fumigatus environmental isolate, collected in 2015. The TR34/L98H mutation, linked to environmental transmission route of azole resistance, was the most frequently detected mutation (N = 4; 1.4%). Our findings underline the demand for correct identification and susceptibility testing of Aspergillus isolates.